2013
DOI: 10.1111/jcmm.12120
|View full text |Cite
|
Sign up to set email alerts
|

Acute treatment with relaxin protects the kidney against ischaemia/reperfusion injury

Abstract: Although recent preclinical and clinical studies have demonstrated that recombinant human relaxin (rhRLX) may have important therapeutic potential in acute heart failure and chronic kidney diseases, the effects of acute rhRLX administration against renal ischaemia/reperfusion (I/R) injury have never been investigated. Using a rat model of 1-hr bilateral renal artery occlusion followed by 6-hr reperfusion, we investigated the effects of rhRLX (5 μg/Kg i.v.) given both at the beginning and after 3 hrs of reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 55 publications
(71 reference statements)
5
62
2
Order By: Relevance
“…Rln treatment also counteracted free radical-mediated tissue injury in ischemia-reperfusion-induced intestinal and renal injury (2,15). These effects were mediated, in part, by Rln-stimulated increases in SOD-1 expression and/or activity (2,5). This suggests that the mechanism by which endogenous Rln regulates basal superoxide production could differ from that of exogenous Rln, which often produces nonphysiological plasma Rln concentrations.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Rln treatment also counteracted free radical-mediated tissue injury in ischemia-reperfusion-induced intestinal and renal injury (2,15). These effects were mediated, in part, by Rln-stimulated increases in SOD-1 expression and/or activity (2,5). This suggests that the mechanism by which endogenous Rln regulates basal superoxide production could differ from that of exogenous Rln, which often produces nonphysiological plasma Rln concentrations.…”
Section: Discussionmentioning
confidence: 80%
“…An ex vivo study (5) using rat aortic rings incubated with TNF-␣ to stimulate endothelial dysfunction showed that Rln treatment attenuated both superoxide and nitrotyrosine production. Rln treatment also counteracted free radical-mediated tissue injury in ischemia-reperfusion-induced intestinal and renal injury (2,15). These effects were mediated, in part, by Rln-stimulated increases in SOD-1 expression and/or activity (2,5).…”
Section: Discussionmentioning
confidence: 88%
“…First, the definite blood flow of the kidneys was not determined. However, the model of renal I/R used in this study is comparable to that widely used in experiments on renal I/R (Hassoun et al, 2007;Collino et al, 2013;Lee et al, 2013;El Morsy et al, 2015). Second, we used TUNEL staining to evaluate apoptosis of the kidneys in this study, and while TUNEL staining is a sensitive method commonly used for detecting apoptosis (Kao et al, 2010;Lee et al, 2013;Lin et al, 2014;Huang et al, 2015), it is not specific (Elsässer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Renal I/R happens in kidney surgery and kidney transplantation (Snoeijs et al, 2010). Renal I/R increases the production of pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), and decreases the level of anti-inflammatory cytokines, such as interleukin-10 (IL-10) (Collino et al, 2013;Lee et al, 2013;Lin et al, 2014;Tsuda et al, 2014;El Morsy et al, 2015). This increase in pro-inflammatory cytokines and reduction of anti-inflammatory cytokines may enhance inflammatory responses and induce apoptosis, both of which mediate the development of AKI (Lee et al, 2013;Lin et al, 2014;Tsuda et al, 2014;El Morsy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This working hypothesis is based on the following mainstays: ( i ) blood vessels are a physiological target of RLX and their cells express the specific RLX receptor RXFP1 25; ( ii ) RLX up‐regulates NOS expression and nitric oxide production in vascular endothelial cells 26, 27, 28, 29, 30; ( iii ) RLX improves inflammation‐induced endothelial dysfunction and NOS fall 31, 32; and ( iv ) RLX reduces oxidative stress and nitric oxide failure in different animal models of vascular injury 33, 34, 35, 36, 37.…”
Section: Introductionmentioning
confidence: 99%